DEPOSITION OF DIQUAT WITH DIFFERENT SPRAY TIPS, EFFICIENCY ON COMMON WATER HYACINTH, AND EFFECT ON WATER QUALITY - de MARCHI, Sidnei Roberto; Marques, Ricardo Fagundes [UNESP]; Martins, Dagoberto [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2022)
Eichhornia crassipes, known as common water hyacinth, has a high growth rate and produces large amounts of biomass when there are imbalances in water bodies, making it one of the worst aquatic weeds in the world. A study was carried out under small water reservoir field conditions to evaluate the herbicide diquat (960 g ha−1) in controlling this species, at the adult stage development. Four spray tips (AI 11002VS, XR 11002VS and, TXVK-8 with spray volume of 200 L ha−1 and XR 11003VS with 400 L ha−1) were tested. Spraying was performed using a CO2-pressurized sprayer under constant pressure attached to a boat. Plant control was visually evaluated at 1, 3, 7, 11, 14, 21, 29, 60, 87, and 98 days after herbicide application and dry matter accumulation was determined at the end of the experimental period, as well as the spray solution deposition in the application area and water physical and chemical quality. The herbicide diquat was efficient in controlling E. crassipes plants at the dose applied and in development stage of the studied plants, regardless of the type of spray tip at the end of the evaluations. At the beginning of evaluations, the spray tip XR 11002VS was the least effectivity in controlling water hyacinth plants. Spray solution losses were high in all tips tested for control of E. crassipes plants, and the spray tips AI 11002VS and XR 11003VS provided the lowest losses during spraying. No water physical or chemical characteristics were negatively affected by diquat application.
Keywords: Eichhornia crassipes; Herbicide; Reward; Spray Technology; Water plant